Interplay Between Toxoplasma gondii, Autophagy, and Autophagy Proteins - Subauste, Carlos S. (Frontiers in Cellular and Infection Microbiology, 2019)
Survival of Toxoplasma gondii within host cells depends on its ability of reside in a vacuole that avoids lysosomal degradation and enables parasite replication. The interplay between immune-mediated responses that lead to either autophagy-driven lysosomal degradation or disruption of the vacuole and the strategies used by the parasite to avoid these responses are major determinants of the outcome of infection. This article provides an overview of this interplay with an emphasis on autophagy.